Building Bridges: The Effect of Major Infrastructure Development on Trade - Maria Persson; Christian Soegaard; Anna Welander Tärneberg (Lund University, School of Economics and Management, Department of Economics, 2022)
We provide evidence of a positive effect of major infrastructure development on international trade, using the opening of the fixed link between Denmark and Sweden in 2000 (The Oresund Bridge) as a quasi-natural experiment. Our Synthetic Control Method (SCM) constructs a counterfactual Danish-Swedish trade relationship, which represents bilateral trade in the absence of the bridge. Evaluating actual trade against its synthetic counterpart for the period 2001-2008 shows that Danish-Swedish trade was 24.6% larger than it would have been in the absence of the bridge using our preferred specification. The result is robust to standard sensitivity checks. We supplement our analysis with a standard Difference-in-differences (DiD) estimator, which uses fixed effects. The DiD estimator yields a slightly larger trade effect of 26.7%, and is robust to a number of sensitivity analyses, including estimation at the product level. Both our SCM and DiD point to the trade-boosting effects being gradual.
Keywords: F14; F15; 330; Fixed link; bridge; tunnel; transport infrastructure; trade; Synthetic Control Method; Difference-in-differences